Development of the information technology for processing anomalous measurements of strain-gauge systems - Копытчук, Николай Борисович; Тишин, Петр Метталинович; Копытчук, Игорь Николаевич (Eastern-European Journal of Enterprise Technologies, 2015)
The aim of the research is the development of the information technology for processing anomalous measurements of strain-gauge systems to improve the accuracy of estimating the mass of an object with a limited time of weighing. With this, the main problem is the need to describe anomalous situations that may occur on a variety of sensors under uncertainty. This task required the development of an appropriate mathematical approach based on the theory of fuzzy time series, as well as new approaches in determining the degree of comparison of fuzzy situations. In practice, the search for anomalies is proposed to carry out with the help of the algorithms using the specially-designed standard bases, describing the fuzzy situations. It is assumed that the standard bases are formed of a large set of real situations. Experimental results show that using this information technology in processing the signals from a plurality of strain gauges increases the estimation accuracy of the sensor readings by several times.